Multiple bouncy balls in an adolescent girl - Nidhi Kamra; Ankita Tuknayat (Wolters Kluwer Medknow Publications, 2020)
Pilomatricoma is a benign hair follicle hamartoma presenting as a single hard dermal or subcutaneous nodule on the head and neck in children. A 15-year-old girl with multiple bullous pilomatricomas is being presented and the importance of ruling out underlying genetic defects in such patients is being discussed.